EMOJI, A BREAKTHROUGH IN CONTEMPORARY COMMUNICATION (A Literature Review) - I Wayan Dirgayasa (Journal of Language, Literature and Teaching, 2022)
It is a fact that emojis are a growing phenomenon in the last few years. They have gained their popularity with their typical varieties in the digital era across countries in the world. The emojis are used among people as a way to assist the process of conveying emotions in textual communication that lacks nonlinguistic cues. Emojis were created and developed as visual mixed expressions of sentiments, attitudes, or moods for use in modern communication technologies. Then, in more broad perspective and context, in term usages, they are also generally perceived that they do not only have unique semantic and emotional features, but also are closely related to many areas such as marketing, law, education, health, etc. This paper reviews the nature of emoji, the developmental history of emojis, the functions of emojis in communication, and the usages of emojis in a real-digital world interaction and communication. Key words: emoji, function of emojis in communication, and the usages of emoji in digital world.